2021
DOI: 10.3389/fimmu.2020.599647
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Decay Accelerating Factor Primes Human Germinal Center B Cells for Phagocytosis

Abstract: Germinal centers (GC) are sites for extensive B cell proliferation and homeostasis is maintained by programmed cell death. The complement regulatory protein Decay Accelerating Factor (DAF) blocks complement deposition on host cells and therefore also phagocytosis of cells. Here, we show that B cells downregulate DAF upon BCR engagement and that T cell-dependent stimuli preferentially led to activation of DAFlo B cells. Consistent with this, a majority of light and dark zone GC B cells were DAFlo and susceptibl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 50 publications
3
9
0
Order By: Relevance
“…Other studies employing germline C3ar1/C5ar1 -deficient animals showed that B cell-expressed C3aR1/C5aR1 signals drive early activation events (including upregulation of AID and BCL-6), but potential links to GC dynamics and GC-dependent affinity maturation were not addressed 46 . A recent 2021 paper 47 reported DAF downregulation on human GC B cells, largely confirming our findings. The authors suggested that DAF downregulation would enhance phagocytosis of GC B cells and could possibly also facilitate interaction with T cells; mechanisms that we did not directly test in our study but could directly/indirectly impact affinity maturation and positive selection in the GC 48 , 49 , contributing to the phenotypes that we detect in our models.…”
Section: Discussionsupporting
confidence: 92%
“…Other studies employing germline C3ar1/C5ar1 -deficient animals showed that B cell-expressed C3aR1/C5aR1 signals drive early activation events (including upregulation of AID and BCL-6), but potential links to GC dynamics and GC-dependent affinity maturation were not addressed 46 . A recent 2021 paper 47 reported DAF downregulation on human GC B cells, largely confirming our findings. The authors suggested that DAF downregulation would enhance phagocytosis of GC B cells and could possibly also facilitate interaction with T cells; mechanisms that we did not directly test in our study but could directly/indirectly impact affinity maturation and positive selection in the GC 48 , 49 , contributing to the phenotypes that we detect in our models.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, CD55 localised to germinal centres, the sites of B-cell expansion and selection, and the presence of B cells in the germinal centres was confirmed by Pax-5 staining. This finding is supported by recent data showing CD55 localisation in tonsil germinal centres and that its expression on B-cell surfaces regulates their complement-dependent phagocytosis for maintaining homeostasis [38]. Furthermore, our data showed that CD55 staining in lymphoid aggregates was independent of H. pylori status and that their presence was not associated with gastric mucosal CD55 mRNA levels.…”
Section: Discussionsupporting
confidence: 91%
“…This labeling occurs by binding phosphatidylserine that is externalized on the surface of cells undergoing apoptosis (69). Recently, a molecule called decay accelerating factor (DAF) has also been proposed to regulate GC B cell phagocytosis (70). Such signals likely help TBMs distinguish between healthy B cells and B cells undergoing apoptosis.…”
Section: A New Gc Modelmentioning
confidence: 99%